FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI KONTAKTANI DALAM PERENCANAAN PROGRAM PENYULUHAN PERTANIAN (Kasus WKUPP Nyalindung, Kabupaten Sukabumi) - Herawati Herawati; Ismail Pulungan (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
The main objective of this research was to determine the extent of contact-farmer participation in agricultural extension program planning i.e., in collecting data, in compiling the data collected, in attending meeting, in discussing and in giving suggestions, and in authenticating the program and activities that followed. To meet this objective, 30 contact-farmers registered in the Contact-Farmer Association (Gapoktan) in Rural Extension Unit at Nyalindung Subdistrict, District of Sukabumi were interviewed. The research results showed that both the contact-farmers’ internal and external factors were highly correlated with their participation in planning Agricultural Extension program and activities.